THE UTILIZATION OF SEA WATER IN A ESPECIALLY DESIGNED BATTERY (SABRINE SWALL BATTERY) - Mursyidah -; Adhi Susanto; Isnaeni BS (ASEAN Journal of Systems Engineering, 2013)
Batteries are chemical devices to save electricity. device capable of generating a DC voltage, ie by converting chemical energy contained in it into electrical energy through the reaction of electro clams, Redox (Reduction - Oxidation). The battery consists of several cells, these cells become energy storage in the form of chemical energy. Negative electrode called the cathode, which serve as electron donors. Positive electrode called the anode which serves as an electron acceptor. Between the anode and the cathode current will flow from the positive pole (anode) to the negative pole (cathode). While the electrons will flow from ktoda toward the anode.In this study, the batteries are designed to use sea water as electrolyte. Voltage measured for one cell is 0,75 Volt and measurable current of 100mA, to get the required voltage is 10 Volts 15 cells arranged in series. Testing is done by loading a flashlight with 5 LED, the results of this special design battery capable of powering 5 LED for seven days without stopping, this suggests that there are large energy stored in batteries. After charging the battery energy runs out of energy again just by replacing the sea water as electrolyte. These batteries are designed to be placed in the beach area and waterfront, it is intended that the sea water needs as the electrolyte can be easily obtained. The especially designed battery is one of the low technology and easy to be made, because the necessary materials readily available in the manufacture of batteries, the battery does not require extra maintenance, environmentally friendly and can be used for twenty-four hours as long as there is sea water.